Zooarchaeology in Practice Case Studies in Methodology and Interpretation in Archaeofaunal Analysis (Springer International Publishing, 2018)
Zooarchaeology in Practice unites depth of treatment with broad topical coverage to advance methodological discussion and development in archaeofaunal analysis. Through case studies, historical accounts, and technical reviews authored by leading figures in the field, the volume examines how zooarchaeological data and interpretation are shaped by its methods of practice and explores the impact of these effects at varying levels of investigation. Contributing authors draw on geographically and taxonomically diverse datasets, providing instructive approaches to problems in traditional and emerging areas of methodological concern. Readers, from specialists to students, will gain an extensive, sophisticated look at important disciplinary issues that are sure to provoke critical reflection on the nature and importance of sound methodology. With implications for how archaeologists reconstruct human behavior and paleoecology, and broader relevance to fields such as paleontology and conservation biology, Zooarchaeology in Practice makes an enduring contribution to the methodological advancement of the discipline.